Off The Label ? Not Uncommon - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2007)
In the field of medicine including ophthalmology since a long while there has been a practice to use an approved drug for an indication not approved by the regulating authorities i.e. off the label use. This trend is becoming more wide spread in ophthalmic practice all over the world like the use of intravitreal: